2005
DOI: 10.1007/s00066-005-1290-1
|View full text |Cite
|
Sign up to set email alerts
|

Radiobiological Investigation of Dose-Rate Effects in Intensity-Modulated Radiation Therapy

Abstract: Even at fraction times of 15-30 min the protracted dose delivery increases the survival rates in cell culture. The altered survival rates indicate the importance of the dose rate in the effectivity of IMRT. Besides physical parameters the consideration of biological factors might contribute to the optimization of IMRT in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 25 publications
(13 reference statements)
2
38
0
Order By: Relevance
“…In addition, the IMSRT approach will increase the time for planning, dose delivery and integral dose to the brain [13]. Furthermore, Sterzing et al [38] reported significantly increased survival rates (6%) of human lymphoblasts and melanoma cells in vitro after protracted dose delivery of 2 Gy compared to the usually used high dose rate [38].…”
Section: Late Toxicitymentioning
confidence: 99%
“…In addition, the IMSRT approach will increase the time for planning, dose delivery and integral dose to the brain [13]. Furthermore, Sterzing et al [38] reported significantly increased survival rates (6%) of human lymphoblasts and melanoma cells in vitro after protracted dose delivery of 2 Gy compared to the usually used high dose rate [38].…”
Section: Late Toxicitymentioning
confidence: 99%
“…It is generally accepted that the trialand-error process typical of conformal planning has shifted inverse planning (IP) to an iterative adjustment of prescription, weights and penalties to obtain the desired dose distribution. Various IP systems are now commercially available, applying quadratic dose-based objective functions, anatomy-based segmentation and segment weighting [8,14,19], or the dynamic penalized likelihood method [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that the trialand-error process typical of conformal planning has shifted inverse planning (IP) to an iterative adjustment of prescription, weights and penalties to obtain the desired dose distribution. Various IP systems are now commercially available, applying quadratic dose-based objective functions, anatomy-based segmentation and segment weighting [8,14,19], or the dynamic penalized likelihood method [16].The determination of prescription parameters of an objective function is a key issue in IP. If a constraint set has been determined for an individual patient, it is not obvious to which extent it holds for an IMRT class solution and whether it is specific to a treatment-planning system (TPS).…”
mentioning
confidence: 99%
“…In IMRT dose measurements, the dose integration time is often significantly longer than for conventional measurements. [76][77][78][79][80][81] A large fraction of the delivered dose is due to collimator and linear accelerator head leakage, so the dose needs to be measured for all beams, even those radiation beams that do not directly intercept the ionization chamber ͑for example, for serial tomotherapy indices where the chamber position is far from the beam portals͒.…”
Section: Iia3 Electrometer and Cable Performancementioning
confidence: 99%